2007
DOI: 10.1080/03602530701497804
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS-Based Metabolomics in Drug Metabolism

Abstract: Xenobiotic metabolism, a ubiquitous natural response to foreign compounds, elicits initiating signals for many pathophysiological events. Currently, most widely used techniques for identifying xenobiotic metabolites and metabolic pathways are empirical and largely based on in vitro incubation assays and in vivo radiotracing experiments. Recent work in our lab has shown that LC-MS-based metabolomic techniques are useful tools for xenobiotic metabolism research since multivariate data analysis in metabolomics ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
147
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(161 citation statements)
references
References 50 publications
1
147
1
Order By: Relevance
“…Therefore, effective methods for prioritizing, studying, and ultimately identifying uncharacterized metabolites is a critical development for LC/MS based metabolomics [5][6][7][8][9][10]. Here we discuss current LC/MS metabolomic approaches (detailed elsewhere [2,4,11,12]) and their integration into 'Metabolite Atlases' to facilitate annotation and prioritization of uncharacterized metabolites. …”
mentioning
confidence: 99%
“…Therefore, effective methods for prioritizing, studying, and ultimately identifying uncharacterized metabolites is a critical development for LC/MS based metabolomics [5][6][7][8][9][10]. Here we discuss current LC/MS metabolomic approaches (detailed elsewhere [2,4,11,12]) and their integration into 'Metabolite Atlases' to facilitate annotation and prioritization of uncharacterized metabolites. …”
mentioning
confidence: 99%
“…Moreover, metabolomics, a tool for measuring small-molecule metabolite profiles and fluxes in biological matrices (Chen et al, 2007), was used to monitor the effect of hPXR activation and CYP3A4 induction on APAP metabolism. The data revealed that hPXR activation and CYP3A4 induction enhanced APAP-induced liver injury.…”
mentioning
confidence: 99%
“…To achieve that, IPF is a stable isotope-based metabolomics approach using compound labeled with 2 H, 13 C, 15 N, or 18 O that can be used to facilitate identi cation of the metabolites. 42,48,49) e stable isotope ratio (1 : 1) from spiked native and isotope-labeled compounds were used for metabolite signal detection.…”
Section: Methods Of Mass Spectrometry In Dis-covery Of Exposure Markermentioning
confidence: 99%